Analisis Hubungan antara Penguasaan Ushul Fiqh dan Tingkat Pemahaman Materi Fiqh di Semester VII Ma’had Aly Imam Bukhari - Ridha, Achmad Rasyid; Haerullah, Haerullah; Rahadi, Rahmad; Saepudin, Ade; Nasron, Mohammad Alif; Rahmahadikusuma, Raditya (TSAQOFAH, 2024)
This study was conducted to analyze the relationship between the mastery of Ushul Fiqh and the level of understanding of Fiqh among seventh-semester students at Ma’had Aly Imam Bukhari. Ushul Fiqh is a crucial discipline in Islamic law studies, as it serves as a foundation for understanding and applying Islamic legal rulings. Therefore, the aim of this research is to determine whether mastery of Ushul Fiqh significantly contributes to a deeper understanding of Fiqh. This research uses a qualitative method with a descriptive approach. Data was collected through in-depth interviews with several seventh-semester students studying both Fiqh and Ushul Fiqh. Thematic analysis was used to explore the relationship between mastery of Ushul Fiqh and the understanding of Fiqh. The results show a significant relationship between the mastery of Ushul Fiqh and the understanding of Fiqh. Students with a strong grasp of Ushul Fiqh were able to understand Fiqh terms more easily and had better analytical skills in evaluating various scholarly opinions. In conclusion, the mastery of Ushul Fiqh positively contributes to a better understanding of Fiqh. Thus, improving the teaching of Ushul Fiqh is expected to enhance students' comprehension of Fiqh and improve the quality of Islamic education in academic institutions.